The effect of perceived stress on binge eating behavior among Chinese university students: a moderated mediation model - Li, Chunlu; Gu, Jing; Li, Yixin; Xia, Baijuan; Meng, Xiaolu (Frontiers in Psychiatry, 2024)
Previous studies have demonstrated a strong link between perceived stress and binge eating behavior, but the psychological mechanisms underlying such phenomenon are not fully understood. The present study further addressed this issue in a life history framework, focusing on life history strategy and distress tolerance. Firstly, we investigated the mediation role of life history strategy on the relationship between perceived stress and binge eating behavior. Secondly, we examined the moderation role of distress tolerance on the effect of perceived stress on life history strategy, as well as on the direct effect of perceived stress on binge eating behavior. we analyzed data from1342 Chinese university students. Results indicated that life history strategy mediates the relationship between perceived stress and binge eating behavior; distress tolerance has significant moderating effects on the direct effect of perceived stress on binge eating behavior and their indirect effect via life history strategy. Therefore, distress tolerance skills training and life history-based interventions might be potentially effective ways to reduce binge eating behavior triggered by perceived stress.